Is organic farming worth its investment? The adoption and impact of certified pineapple farming in Ghana - Linda Kleemann; Awudu Abdulai; Mareike Buss (Kiel Institute for the World Economy (IfW), 2013)
Global food markets demand the adoption of food standards by small-scale farmers in developing countries when they enter international markets. While a conventional certification with GlobalGAP can be a market entry condition for conventional food, especially for horticultural products, organic certification is required for the growing organic food market that is usually associated with higher prices. This study analyzes the adoption and profitability of organic certified farming, using recently collected farm-level data of 386 Ghanaian pineapple farmers. We employ an endogenous switching regression model to examine the adoption and impact of organic certification on the return on investment (ROI). The empirical results indicate that both organic certification and GlobalGAP certification result in a positive ROI. However, organic certified farming yields a significantly higher ROI than GlobalGAP certified farmers, mainly due to the price premium on the organic market. Thus, certified organic farming is found to be the more profitable venture.
Keywords: O13; Q13; Q17; Q56; 330; return on investment; impact assessment; organic agriculture; GlobalGAP certification; contract farming